(untitled) (Journal of Pedagogical Inventions and Practices, 2023)
Arguments Against Increasing Grammar in a Foreign Language Course Many native speakers make a large number of grammatical errors and slips, but this is not unacceptable. Grammatically very correct, the absence of errors betrays educated foreigners. Grammar reference books explain grammar using so many specific grammar terms that it is almost impossible to understand anything for the first time.